Calretinin, parvalbumin and calbindin immunoreactive interneurons in perirhinal cortex and temporal area Te3V of the rat brain: qualitative and quantitative analyses - Barinka, Filip; Salaj, Martin; Rybář, Jan; Krajčovičová, Eva; Kubová, Hana; Druga, Rastislav (Brain research, 2012)
The perirhinal cortex (PRC) composed of areas 35 and 36 forms an important route for activity transfer between the hippocampus-entorhinal cortex and neocortex. Its function in memory formation and consolidation as well as in the initiation and spreading of epileptic activity was already partially elucidated. We studied the general pattern of calretinin (CR), parvalbumin (PV) and calbindin (CB) immunoreactivity and its corrected relative optical density (cROD) as well as morphological features and density of CR and PV immunoreactive (CR+, PV+) interneurons in the rat PRC. Neighboring neocortical association area Te3V was analyzed as well. The PRC differed from the Te3V in higher CR and lower PV overall immunoreactivity level. On CR immunostained sections, the difference between high cROD value in area 35 and low cROD value in area Te3V reached statistical significance (p<0.05). The pattern of CB immunoreactivity was similar to that of the neocortex. Vertically oriented bipolar neurons were the most common morphological type of CR+ neurons, multipolar neuronal morphology was typical among PV+ neurons and vertically oriented bipolar neurons and multipolar neurons were approximately equally frequent among CB+ neurons. The density of CR+ and PV+ neurons was stereologically measured. While the density of PV+ neurons was not significantly different in PRC when compared to Te3V, density of CR+ neurons in area 35 was significantly higher by comparison with Te3V (p<0.05). Further, the overall neuronal density was measured on Nissl stained sections and the proportion of CR+ and PV+ interneurons was expressed as a percentage of the total neurons counts. The percentage of CR+ interneurons was higher in area 35 by comparison with area Te3 (p<0.05), while the percentage of PV+ interneurons did not significantly differ among the examined areas. In conclusion, the PRC possesses specific interneuronal equipment with unusually high proportion of CR+ interneurons, what might be of importance for the presumed gating function of PRC in normal and diseased states.
Keywords: Calbindins; Interneurons; Parvalbumins; krysa rodu Rattus; kalbindiny; mozková kůra; parvalbuminy; S100 Calcium Binding Protein G; kalbindin 2; Animals; Rats; neurony; interneurony; zvířata; Calbindin 2; Neurons; S100 kalcium vázající protein G; Cerebral Cortex